Formas de Resistência Africanas às Autoridades Portuguesas no Século XVIII: A guerra de Murimuno e a tecelagem de machira no norte de Moçambique - Luís Frederico Dias Antunes (Cadernos de Estudos Africanos)
The purpose of this paper is to discuss different forms of African resistance both against the Portuguese colonial presence and the external commercial pressure in Mozambique, in the eighteenth century. In the first case, it studies the violent attacks on the expeditionary Portuguese troops perpetrated by a number of belligerent Makua chieftains, in 1753. In contrast, the second case is mainly of economic and cultural nature and deals with the growing cultivation of cotton and the production of native cloths (machiras) as a way of preserving customs and identity thus facing the imposition of consumption and use of Indian textiles.